Optical Activity of an Asymmetric Substance - Frida Ulfah Ermawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2010)
This paper reported the investigation on the property of optical activity from three different isomers of L-, Dand DL–alanine (CH3CHNH2CO2H), a proposed radiation dosimetric material. The aim was to confirm the impact of attachment of -carbon atom of the systems to the four different groups, that is, the -carbon or methyl group, H-group, CO2H-group and NH2-group, to their response to any incoming plane-polarized light. Optical activity of a substance is a measure of the ability of a substance to rotate a plane of polarization, if solution of the substance is placed in the path of plane-polarized light. A polarimeter of Perkin-Elmer Model 141 with a Sodium lamp of 584-nm wavelength (D-line) and equipped with a digital counter was occupied in this work to measure the number of degrees of rotation of plane-polarized light at room temperature due to 8.3% concentration of each L-, D- and DL–alanine solutions. It was obtained that molecules of L-isomer rotate the counter of the polarimeter clockwise, from the observer’s point a view. While the molecules of D-isomer rotate the counter anti clockwise, at the similar amount of rotation. These results confirm the asymmetric structure belong to the -alanine system. Molecules of DL-isomer, however, do not rotate the counter at all. The existence of similar number of the D- and L-molecules in the DL-solution is the cause.